Bumi Kotak: Krisis Epistemologi Islam Rekonstruksi Paradigma Pendidikan Islam di Era Disorientasi Pengetahuan - Asep Sutisna; Musa Asy’ari; Mahasri Shobahiya (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2025)
The phenomenon of the “Flat Earth” or “Bumi Kotak” emerging in digital public spaces today is not merely a debate about the Earth’s shape, but a symbol of the epistemological crisis within the Muslim community. This crisis reflects a disconnection between revelation (al-waḥy), reason (al-‘aql), and empirical experience (al-tajrībah), leading to disorientation in knowledge. This paper aims to describe the Bumi Kotak phenomenon as a manifestation of epistemological crisis, analyze its root causes, and propose a model for reconstructing the paradigm of Islamic education based on tauhidic epistemology. Using a qualitative-descriptive approach with a hermeneutic-philosophical paradigm, this study analyzes classical and contemporary Islamic works by scholars such as al-Attas, al-Faruqi, and Nasr. The findings reveal that the epistemological crisis stems from the loss of tauhidic awareness in modern fragmented and secular knowledge systems. Islamic education must reintegrate revelation, reason, and empirical knowledge into a unified tauhidic epistemology that emphasizes intellectual ethics and adab of thinking. Such reconstruction can guide Islamic education toward a more critical, civilized, and transformative framework in the digital age.